THE ASSOCIATION HACQUETIO-FAGETUM KOŠIR 1962 (AREMONIO-FAGION) IN CROATIA - Trinajstić, Ivo; Pavletić, Zinka (Hacquetia, 2015)
The ass. Hacquetio-Fagetum has been analyzed floristically at several localities in north-western Croatia (Velika Kapela, Samoborsko gorje, Cesargradska gora, Brezovica, Strahinjščica, Ivanščica) just in the area where the highest concentration of the relict Illyricoid elements has been registered. On the occasion, the data on the floristic composition of the ass. Hacquetio-Fagetum based on our own researches are shown in the analytical table (Tab. 1), consisting of 9 relevés. By the analysis of the floristic composition it was found that the ass. Hacquetio-Fagetum comprises 119 species. The number of species by relevé is between 42 and 73, or 60 (59.8) on the average. In all relevés 4 species have been registered, and in more than 50% of relevés 37 species or 25.3 % of the total floristic composition were registered. In only one relevé 53 species or 36.3 % of the total floristic composition were registered. In Table 2, a comparative presentation is given in synthetic form of a total of 63 relevés. On this basis of the data presented, a total of 202 species have been registered in the floristic composition of the ass. Hacquetio-Fagetum.